Mitigation of implosion energy from aluminum structures. (1st December 2016) - Matos, Helio; Shukla, Arun
Highlights: Hydrostatic pressure initiated implosion of polyurea coated structures is studied. New energy scheme is developed to measure the energy emitted during implosion. Energy values measured agree with the theoretical models. Coating structures with polyurea can significantly reduce energy pulses emitted. Energy release predicted based on a collapse volume analysis. Abstract: This study aims to develop an experimental scheme to determine the localized energy emitted during the dynamic collapse of aluminum structures. Upon collapse, these structures release damaging pressure pulses into the surrounding fluid; to mitigate this effect, the structures are coated with polyurea. The new energy scheme is used to analyze the energy emission from coated structures. Specifically, aluminum tubular structures with polyurea coatings on their interiors or exteriors are used. Furthermore, the technique combines the information obtained from pressure sensors, located near the collapsing structure, and high-speed images taken during the collapse event. These images are processed through a 3D Digital Image Correlation technique to obtain full deformation and velocity fields. Results show that the energy history can be successfully obtained experimentally. Moreover, the energy emitted from coated aluminum structures is significantly less than the uncoated structures; more so with interior coated structures, and doubling the coating volume does not significantly improve this mitigation effect. Additionally, collapse volume has a direct relationship with energy and is a dominant factor in determining the energy release.